Vitamin D and health issues – questioned benefits. (December 2014) - Pines, A.
Abstract The easy access to measurement of serum 25-hydroxyvitamin D (vitD) levels created a surge in interest to learn more of its potential health benefits and its association with prevention of chronic diseases. VitD effects on bone and fracture risk were studied extensively, resulting in clinical guides that stress the need for adequate vitD supplementation. In addition, data are accumulating on its relevance to cardiovascular disease, cancer, cognition and other health domains. Recent studies and meta-analyses seem to lower this enthusiasm concerning the expected good outcomes of higher vitD levels in regard to reduction of risk for major chronic diseases in the general population. However, data are more supportive on various benefits in the case of vitamin D deficiency states, especially in older people. The following article is a short review of the latest developments in this regard.